Virtual & augmented reality technology enhanced engineering learning - Lee, Yong Sheng (Nanyang Technological University, 2020)
Virtual Reality (VR) and Augmented Reality (AR) have been one of well-known topics among publics in the past few years. Recently, they are treated to be having another breakthrough during 5G commercialisation in the past 2 to 3 years. Although VR & AR Technology has been already widely and maturely applied in various industries such as gaming, e-commerce (online shopping), tourism, industrial training or etc. It is still yet to be exploring its expansion on application in education for training purpose.The aim of this project is to propose a concrete solution to apply VR/AR/MR in the education for engineering students in a tertiary institution, Institute Technical Education (ITE) in Singapore, by learning to identify, assemble and disassemble of the key Hydraulic System components from digitising a real jet model Lear24 which is placed in the laboratory class. The proposed method is implemented with Hololens, Unity3D 2018.4.6f1 (64-bit) and Visual Studio Community 2019. The user can view a 3D immersive VR-environment of hydraulic system during the tutorial lesson. The student learns the contents of the course such as identification, assembly and disassembly of the key components of the hydraulic system, fluid flow direction of hydraulic system in order to fulfil the learning objective of the course. The learning journey will be reviewed by following an in-process assessment session.